2017
DOI: 10.1142/s0218213017600065
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Portfolio Methods for Optimal Planning: An Empirical Analysis

Abstract: Combining the complementary strengths of several algorithms through portfolio approaches has been demonstrated to be effective in solving a wide range of AI problems. Notably, portfolio techniques have been prominently applied to suboptimal (satisficing) AI planning.\ud \ud Here, we consider the construction of sequential planner portfolios for domainindependent optimal planning. Specifically, we introduce four techniques (three of which are dynamic) for per-instance planner schedule generation using problem i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A second per-instance algorithm selection approach for AI planning has been considered by Rizzini et al (2015Rizzini et al ( , 2017. Their PLANZILLA system can be seen as an application of the previously outlined * ZILLA approach (Cameron et al, 2017) to AI planning.…”
Section: Planzillamentioning
confidence: 99%
See 1 more Smart Citation
“…A second per-instance algorithm selection approach for AI planning has been considered by Rizzini et al (2015Rizzini et al ( , 2017. Their PLANZILLA system can be seen as an application of the previously outlined * ZILLA approach (Cameron et al, 2017) to AI planning.…”
Section: Planzillamentioning
confidence: 99%
“…Using all planners that participated in the optimal track of the 2014 International Planning Competition (IPC-14), PLANZILLA was found to substantially outperform these individual planners and achieve performance close to that of the VBS (Rizzini et al, 2015(Rizzini et al, , 2017. However, when evaluated on a set of testing instances dissimilar from those used for training, it was found that dynamic algorithm scheduling approaches performed better than PLANZILLA; these approaches dynamically construct an algorithm schedule by performing multiple stages of per-instance algorithm selection, using not only features of the planning instance i to be solved, but also taking into account which component planners have already been run on i, without success, in earlier stages of the schedule.…”
Section: Planzillamentioning
confidence: 99%
“…SATZilla (Xu et al, 2012) has been rather influential also outside the SAT domain. For example, in AI planning, Planzilla (Rizzini, Fawcett, Vallati, Gerevini, & Hoos, 2017) and its improved variants (model-based approaches) were all inspired by the random forests and regression techniques proposed by SATZilla/Zilla. Similarly, for Satisfiability Modulo Theories (SMT) problems, MachSMT (Scott, Niemetz, Preiner, Nejati, & Ganesh, 2021) was recently introduced and its essential parts also rely on random forests.…”
Section: Related Workmentioning
confidence: 99%
“…AllPACA is a portfolio that selects the most promising optimal planner to run on a given planning task. A comparison of static and dynamic portfolio techniques, focused on optimal planning, has been recently done by Rizzini et al…”
Section: Related Workmentioning
confidence: 99%